Respostas

2013-04-17T15:40:19-03:00

Sendo 
z1 = 2 + 3i 
z2 = -6 + i 
A)z1 + z2

z1 + z2 = (2 + 3i) + (- 6 + i) = 2 + 3i - 6 + i = - 4 + 4i 

B)z1 - z2

z1 - z2 = (2 + 3i) - (- 6 + i) = 2 + 3i + 6 - i = 8 + 2i

C)z1 . z2
aqui é preciso aplicar a propriedade distributiva e lembrar que i² = - 1

z1 . z2 = (2 + 3i) . (- 6 + i) = - 12 + 2i - 18i + 3i²

z1 . z2 = - 12 + 2i - 18i + 3 . (-1) = - 12 - 3 + 2i - 18 i = - 15 - 16i

D)z1/z2

z1 / z2 = (2 + 3i) / (- 6 + i) 
multiplica pelo conjugado do denominador

z1 / z2 = [(2 + 3i) (-6 - i)] / [(- 6 + i) (-6 - i)

z1 / z2 = (-12 - 2i - 18i - 3i²) / (36 - i²)

z1 / z2 = (-12 - 2i - 18i - 3(-1)) / (36 - (-1))

z1 / z2 = (-12 - 2i - 18i + 3) / (37)

z1 / z2 = (-9 - 20i) / (37) 

z1 / z2 = - 9 - 20i / 37

1 5 1
2013-04-17T15:42:26-03:00

a) 31 + 82 =

b) 31- 82=

c) 82-31=

d) 31*82=

e)31/82

f)82/31

1 5 1